Emotion Induced Monoamine Neuromodulator Release Affects Functional Neurological Disorders - Liang, Fei; Xu, Qiuyue; Jiang, Mingchen; Feng, Rou; Jiang, Shan; Yuan, Bin; Xu, Shijun; Wu, Ting; Wang, Fushun; Huang, Jason H. (Frontiers in Cell and Developmental Biology, 2021)
Functional neurologic disorders (FND), also called conversion disorder (previously called hysteria), can show almost all the symptoms of other neurological diseases, including both physical (for example, seizure, weakness, fatigue) and psychological (for instance, depression, anxiety) symptoms. In spite of our general knowledge about emotional processes and developmental defects in the formation of somatic symptoms, there is still no systemic and comprehensive research on the effects of emotional developmental variables in FND. Recently, both experimental and theoretical emotion studies have been greatly increased, such as prediction error, conceptual act model, basic emotional theory, and monoamine neuromodulator based three primary emotions. In addition, a large amount of evidence has confirmed psychosocial adversity (such as stressful life events, interpersonal difficulties) as an important risk factor for FND. Here, we review recent advances about emotional stress on FND, and pay special attention to the effects of monoamine neuromodulators, such as how norepinephrine, serotonin affect behaviors. Then, we discussed the significance of these changes for FND, which may contribute to clarifying the pathogenesis of FND, and thus provide potential therapeutic drug targets or psychological intervention methods in the future.